Figuring out figuration a cognitive linguistic account - Peña Cervel, M. Sandra (Figurative thought and language,, 2022)
"This book combines explanatory breadth with analytical delicacy. It offers a comprehensive study of a broad array of traditional figures of speech by systematizing linguistic evidence of the cognitive processes underlying them. Such processes are explicitly linked to different communicative consequences, thus bringing together pragmatics and cognition. This type of study has allowed the authors to provide new definitions for all the figures while making their dependency relations fully explicit. For example, hypallage, antonomasia, anthimeria, and merism are studied as variants of metonymy, and analogy, paragon, and allegory as variants of metaphor. An important feature of the book is its special emphasis on the combinations of figures of speech into conceptually more complex configurations. Finally, the book accounts for the principles that regulate the felicity of figurative expressions. The result is a broad integrative framework for the analysis of figurative language grounded in the relationship between pragmatics and cognition"--